2021
DOI: 10.17159/2309-8775/2021/v63n2a5
|View full text |Cite
|
Sign up to set email alerts
|

South African infrastructure condition - an opinion survey for the SAICE Infrastructure Report Card

Abstract: The South African Institution of Civil Engineering (SAICE) Infrastructure Report Cards of 2006, 2011 and 2017 reported that much of the South African infrastructure is in a poor condition. To augment the recent 2017 Report Card, a survey was, for the first time, conducted amongst SAICE members to obtain their opinion on the condition of infrastructure (in terms of a grading), the trend of the condition over time, as well as the reasons for the individual's grading. The 669 respondents indicated that, apart fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Naresh Pather, president of Consulting Engineer South Africa (CESA), corroborated this by saying that it was concerning that a considerable number of engineers are leaving the industry to seek employment opportunities in more fulfilling economic parts of the globe in related industries (Cokayne, 2019). A survey which Rust et al (2021) conducted revealed that among 1367 SAICE members, 932 (68%) indicated that they are willing to continue to be a part of the country's labour force. However, aspects such as over-politicisation of infrastructure, a lack of training and development and career paths, underremuneration, corruption and poor leadership prevent them from remaining in the labour force.…”
Section: South African Engineering Industry Work Contextmentioning
confidence: 99%
“…Naresh Pather, president of Consulting Engineer South Africa (CESA), corroborated this by saying that it was concerning that a considerable number of engineers are leaving the industry to seek employment opportunities in more fulfilling economic parts of the globe in related industries (Cokayne, 2019). A survey which Rust et al (2021) conducted revealed that among 1367 SAICE members, 932 (68%) indicated that they are willing to continue to be a part of the country's labour force. However, aspects such as over-politicisation of infrastructure, a lack of training and development and career paths, underremuneration, corruption and poor leadership prevent them from remaining in the labour force.…”
Section: South African Engineering Industry Work Contextmentioning
confidence: 99%
“…For instance, their outcomes have been utilized to promote assessments of airport asset surfaces [28], new measurement systems for bridge evaluation [29] or water distribution networks [30], risk analyses for water infrastructure failure [31], and prioritization methods for subway investments based on functional failure impacts [32]. Other publications have focused on how an evaluation has been conducted [33], opinions about IRCs themselves [34], or comparisons related to policy actions and their resulting outcomes [35].…”
Section: Introductionmentioning
confidence: 99%